Media, edukacja i tożsamość etniczna – na przykładzie mniejszości Sami - Gmerek, Tomasz (Wydawnictwo Naukowe UAM, 2012)
The article is devoted to the discussion of media and education as factors of ethnic assimilation and on the other hand as a factor of the revitalization of an indigenous culture. The study analyses the position of the Sami language in the educational system and modern media in Scandinavian countries. It focuses on language as the main cultural factor of Sami ethnic identity. The author emphasizes the assimilation and marginalization process of minority language policy in Norway, Sweden, and Finland, and the possibilities of language revitalization in contemporary Sami society.
Media, Education and Ethnic Identity – Sami Minority Study
Keywords: Sami; media; education; ethnic identity; language; assimilation; revitalization